Environmental Pollutant Anthracene Induces ABA-Dependent Transgenerational Effects on Gemmae Dormancy in Marchantia polymorpha - Tolopka, Juan Ignacio (2024)
Anthracene, a polycyclic aromatic hydrocarbon (PAH) from fossil fuel combustion, poses significant environmental threats. This study investigates the role of abscisic acid (ABA) in the anthracene tolerance of the liverwort Marchantia polymorpha using mutants deficient in ABA perception (Mppyl1) or biosynthesis (Mpaba1). In this study, we monitored the role of ABA in the anthracene tolerance response by tracking two ABA-controlled traits: plant growth inhibition and gemmae dormancy. We found that the anthracene-induced inhibition of plant growth is dose- dependent, similar to the growth-inhibiting effect of ABA, but independent of ABA pathways. However, gemmae dormancy was differentially affected by anthracene in ABA-deficient mutants. We found that gemmae from anthracene-exposed WT plants exhibited reduced germination compared to those from mock-treated plants. This suggests that the anthracene exposure of mother plants induces a transgenerational effect, resulting in prolonged dormancy in their asexual propagules. While Mppyl1 gemmae retained a dormancy delay when derived from anthracene-exposed thalli, the ABA biosynthesis mutant Mpaba1 did not display any significant dormancy delay as a consequence of anthracene exposure. These results, together with the strong induction of ABA marker genes upon anthracene treatment, imply that anthracene-induced germination inhibition relies on ABA synthesis in the mother plant, highlighting the critical role of MpABA1 in the tolerance response. These findings reveal a complex interplay between anthracene stress and ABA signaling, where anthracene triggers ABA-mediated responses, influencing reproductive success and highlighting the potential for leveraging genetic and hormonal pathways to enhance plant resilience in contaminated habitats.